MEDIUM BELUDRU: Mangurupa dan Keberlanjutan Seni di Bali - Putra, I Gede Jaya (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2020)
This article discusses the velvet medium used as a strategy for the sustainability of art in Bali. Based on observations in the field with Badung Regency as an observation location whose growth has been categorized as urbanites in accordance with the characteristics of contemporary art. The study focuses on the Mangurupa community with its sustainability strategy which can be used as a process of awareness of current cultural values, in harmony with the development of the Balinese art scene. Sources of data obtained through a qualitative approach using descriptive analysis method with interview techniques. The theory used is semiotics by Charles Sanders Peirce in the form of representations, objects and interpretations to understand the signs in the work. The present work shows the results of understanding the velvet medium related to the phenomena conveyed. With the awareness of using the medium, the Mangurupa community is able to give a new color to the current art movement. Keywords: Contemporary Art, Mangurupa, Medium, Sustainability, Velvet.